Wolbachia in the Drosophila saltans subgroup: effects on fitness and reproductive isolation - Guzman Sarmiento, Yoan Camilo (2021)
Population genetics and speciation process studies owe tribute to a small group of Neotropical species that caught the attention of Theodosius Dobzhansky. During his visits to Brazil, Dobzhansky noticed that Drosophila species from the saltans and the willistoni groups, widely distributed throughout Central and South America, presented a wide variety of cryptic species, which can be recognized only by details of the male genitalia. Such characteristics suggested that these groups were under speciation process. Among the most studied models, he highlighted the seven species of the saltans subgroup species, which show reproductive isolation but generate hybrids in the laboratory. Later, two of these species, D. prosaltans and D. septentriosaltans, were revealed to be infected by Wolbachia. This infection may play a relevant role in speciation because it can alter reproductive behavior, besides causing death or sterility of hybrids, especially males. This work aimed to investigate the phenotypic consequences of Wolbachia infection in a Brazilian strain of D. prosaltans (Pro101) and a Panamanian strain of D. septentriosaltans (SepPLR2). We assembled intraspecific crosses between infected and antibiotic-treated strains, evaluated the pre and post-mating components of reproductive isolation, and simulated the spread of infection in an uninfected population. Our results suggested that Wolbachia enhances, through different processes, the fitness of Pro101 and SepPLR2, while ensuring their survival and reproduction in these hosts. We also investigated the role of Wolbachia in reproductive isolation between Pro101 and a Mexican strain of D. saltans (Sal02). To do this, we set up interspecific crosses and evaluated the pre and post-mating components of reproductive isolation. The results of this second study suggested that infection does not interfere with the isolation of these species. However, we confirmed that the cross involving females of D. saltans and males of D. prosaltans produces sterile males, which added to further evidence, led us to the hypothesis that another endosymbiont may be responsible for the reproductive isolation between them.Keywords: Wolbachia. Drosophila prosaltans. Drosophila septentriosaltans. Pre and post-mating isolation mechanisms. Mate recognition. Asymmetric hybrid male sterilit